Expertise and the control of interception in table tennis - Sheppard, A.; Li, F.-X. (European Journal of Sport Science, 2007)
The variability in elite table tennis players' bat movement direction was shown qualitatively by Bootsma et al. (1990) to "funnel" or become reduced towards bat-ball contact. Scott et al. (1997) showed that novice long jumpers' foot-placement variability followed a similar pattern of reducing variability that was also found previously for experts, suggesting a common mode of control across various interceptive actions and standards of expertise. The aims of this study were as follows: (1) to compare the variability patterns of expert and novice table tennis players to assess the presence of a common mode of control; and (2) to examine the variability patterns of a comprehensive array of bat kinematic measures. Participants returned balls for speed and accuracy. Variability patterns were similar between groups, although magnitudes were smaller for experts' bat direction. Bat direction and orientation showed reducing variability in the approach to contact, whereas bat position, speed, and acceleration did not. The variability in "funnelling" in many kinematic measures suggests an essential role for on-line control in the table tennis forehand drive. The strong similarity in variability patterns between groups is interpreted as evidence of a common mode of control across standards of expertise that is applicable to interception tasks in general.